Circumcision from a Medical and Islamic Perspective - Maeta, Muhammad Yunus; Harahap, Muh. Wirawan; Masdipa, Andi; Mappaware, Nasrudin Andi; Royani, Ida (Journal La Medihealtico, 2025)
Circumcision is a surgical procedure that involves the removal of the foreskin (prepuce) covering the glans penis. This procedure is typically performed to eliminate smegma, which results from the accumulation of fluids in the foreskin area, causing unpleasant odor and increasing the risk of infection. In Islam, circumcision is a religious practice exemplified since the time of Prophet Ibrahim (Abraham), peace be upon him. This literature review discusses circumcision from both a medical and Islamic perspective. The findings indicate that circumcision is performed based on medical indications such as phimosis, paraphimosis, and balanitis, both as a treatment and as a preventive measure against recurrence. Additionally, circumcision has been linked to a reduced risk of urinary tract infections (UTIs) and HIV transmission. In Islamic terminology, circumcision is referred to as khitan. It is strongly grounded in Islamic jurisprudence and is regarded as a significant practice for Muslim males. Circumcision is effective in reducing the incidence of phimosis, paraphimosis, balanitis, as well as the risks of UTIs and HIV transmission. In Islam, khitan is considered part of human nature (fitrah) and is deemed obligatory (wājib) by some schools of thought, while others regard it as a highly recommended (sunnah muakkadah) practice.